MULTI-FACTOR ENTERPRISE METHODOLOGY: AN APPROACH TO ERP IMPLEMENTATION - Gede Rasben Dantes (CCIT Journal, 2011)
As further investigation on the Information and Communication Technology (ICT) investment especially in Indonesia showed that a larger capital of investment does not automatically bring more benefit for the company, for example Enterprise Resource Planning (ERP) system implementation. The present research was aimed at developing a methodology for ERP Implementation which was fundamental problem for achieving a successful implementation. This methodology will be contained some factors that influenced ERP implementation success (technical or non-technical) as an activity each phase. Because, some of methodologies that common used by consultant more concentrating on technical factors without considering non-technical factors. Non-technical factors were involved in the new proposed of ERP implementation methodology, such as: top management commitment, support, and capability; project team composition, leadership, and skill; organizational culture; internal/external communication; organization maturity level; etc. The conclusion of the study was expected to be useful for private or public sectors when implementing ERP in order to gain optimal return value from their investment.